Cochinchinenin C, a potential nonpolypeptide anti-diabetic drug, targets a glucagon-like peptide-1 receptor. Issue 77 (18th October 2017) - Sha, Yijie; Shi, Yunfeng; Niu, Bing; Chen, Qin
Abstract : The glucagon-like peptide-1 (GLP-1) receptor is currently being explored as a therapeutic target for anti-diabetic drugs. Abstract : The glucagon-like peptide-1 (GLP-1) receptor is currently being explored as a therapeutic target for anti-diabetic drugs. GLP-1 analogs possess therapeutic effects similar to those of other anti-diabetic drugs such as guanidine and sulfonylureas but do not cause hypoglycemia and gastrointestinal discomfort. GLP-1 has the ability to reduce blood glucose in a glucose-dependent manner. Several GLP-1 analog agonists have been developed. However, polypeptide drugs are easily degraded by DPP4 in vivo . Therefore, the focus is now on the development of nonpolypeptide anti-diabetic drugs targeting the GLP-1 receptor. In this study, computer-aided drug design was applied to search for potential molecules of this type. Cochinchinenin C, extracted from sangusis draconi, interacted well with GLP-1 receptor via hydrophobic interaction, which was confirmed by fluorescence spectroscopy and molecular simulation. In cell experiments, it was demonstrated that pancreatic beta cells promoted insulin secretion upon treatment with cochinchinenin C, and increases of intracellular cAMP and ATP levels also occurred, indicating GLP-1 receptor activation and glucose metabolism. These results showed that cochinchinenin C has potential for the development of drugs for treating diabetes.